Characteristics of peritoneal dialysis-related infection according to pet ownership: An 8-year single-center experience - Hyeon Gyu Cho; Jeong Geon Lee; Jung Wan Park; Jihee Lim; Nam Hun Heo; Nam-Jun Cho; Samel Park; Hyo-Wook Gil; Eun Young Lee (PLoS ONE, 2026)
With rising pet ownership, concerns regarding pet-related infections during peritoneal dialysis (PD) have increased. This retrospective study analyzed the characteristics of PD-related infections according to pet ownership. A total of 162 PD patients treated at Soonchunhyang University Cheonan Hospital between 2016 and 2023 were reviewed. Patients were grouped by pet ownership and pet type (dog or cat) based on data obtained from PD nurse home visits. Peritonitis, exit-site infection (ESI), and tunnel infection (TI) were defined according to the International Society of Peritoneal Dialysis guidelines, and data on causative organisms and clinical outcomes were collected. Zoonotic microorganism-associated peritonitis episodes were identified in patients with pets. Staphylococcus-associated ESIs (55.6 vs. 16.2%, p = 0.006) were more frequently observed in patients with pets than in those without pets. However, the overall incidence of peritonitis and ESI did not differ significantly between patients with and without pets, and pet ownership was not associated with mortality or PD catheter removal. These findings suggest that while pet ownership may influence the microbial characteristics of PD-related infections, it does not appear to increase overall infection incidence or adverse clinical outcomes.